Effect of a 12-Week Summer Break on School Day Physical Activity and Health-Related Fitness in Low-Income Children from CSPAP Schools. (9th March 2017) - Fu, You; Brusseau, Timothy A.; Hannon, James C.; Burns, Ryan D.
Abstract : Background . The purpose of this study was to examine the effect of a 12-week summer break on school day physical activity and health-related fitness (HRF) in children from schools receiving a Comprehensive School Physical Activity Program (CSPAP). Methods . Participants were school-aged children (N = 1, 232 ; 624 girls and 608 boys;mean age = 9.5 ± 1.8 years) recruited from three low-income schools receiving a CSPAP. Physical activity and HRF levels were collected during the end of spring semester 2015 and again during the beginning of fall semester 2015. Physical activity was assessed using the Yamax DigiWalker CW600 pedometer. HRF measures consisted of body mass index (BMI) and the Progressive Aerobic Cardiovascular Endurance Run (PACER). Results . Results from a doubly MANCOVA analysis indicated that pedometer step counts decreased from 4, 929 steps in the spring to 4, 445 steps in the fall (mean difference = 484 steps;P < 0.001 ; Cohen's d = 0.30) and PACER laps decreased from 31.2 laps in the spring to 25.8 laps in the fall (mean difference = 5.4 laps;P < 0.001 ; Cohen's d = 0.33). Conclusions . Children from schools receiving a CSPAP intervention had lower levels of school day physical activity and cardiorespiratory endurance following a 12-week summer break.